To solve for x, we first need to simplify the equation by combining like terms.
Starting with the given equation: 13x + 24 = 3x - 26
Subtract 3x from both sides of the equation to isolate the variable x:
13x - 3x + 24 = 3x - 3x - 26
10x + 24 = -26
Subtract 24 from both sides of the equation to continue isolating x:
10x + 24 - 24 = -26 - 24
10x = -50
Now, divide by 10 to solve for x:
10x / 10 = -50 / 10
x = -5
Therefore, the solution to the equation 13x + 24 = 3x - 26 is x = -5.
solve for 13x + 24 = 3x - 26
1 answer